If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = -6w + 2(w + -3) Reorder the terms: -2 = -6w + 2(-3 + w) -2 = -6w + (-3 * 2 + w * 2) -2 = -6w + (-6 + 2w) Reorder the terms: -2 = -6 + -6w + 2w Combine like terms: -6w + 2w = -4w -2 = -6 + -4w Solving -2 = -6 + -4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '4w' to each side of the equation. -2 + 4w = -6 + -4w + 4w Combine like terms: -4w + 4w = 0 -2 + 4w = -6 + 0 -2 + 4w = -6 Add '2' to each side of the equation. -2 + 2 + 4w = -6 + 2 Combine like terms: -2 + 2 = 0 0 + 4w = -6 + 2 4w = -6 + 2 Combine like terms: -6 + 2 = -4 4w = -4 Divide each side by '4'. w = -1 Simplifying w = -1
| 16(2x-7)=4(8x+9) | | 3u+2(u+5)=35 | | 152=-4(7x-3) | | -108=-4(-5b-3) | | xcubo+ycubo=35 | | P^4q^6/p^2q^3 | | 2x^3/2*x^1/7 | | (15a4-9a)/3a | | 4-2x=8+0.5x | | (3+ab)(7-ab)= | | (3+v)(5v-6)=0 | | X+6=6x+31 | | 2+5e=12 | | xcosy=ycosx | | -7=1+n | | y=2/3x-19 | | 10(x-9)-9(5-6x)=2(4x-1)+5(1-2x) | | 4|=/2x-1/=12 | | 16÷8/9 | | (5y+3)(4-y)=0 | | 4c-7=3c-7 | | X+23=5x+31 | | 3+11x=5x+9 | | Ln(14)=ln(x) | | -3x+9=-2(3x+3) | | 18x+33=18x+11 | | 15x-30=15x-30 | | .8x+8+.6x=57 | | F(x)=8-ln(9x) | | A=.5(18)(2) | | 5x+13=3x+33+70 | | 8j-8=64 |